Impact of Covid-19 on The Construction and Engineering Industry - Darshankumar Patel, Basweshwar Jirwankar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The global disruption triggered by the Corona Virus pandemic has had a significant influence on society, the environment, and the economy. Only two events world wars and the 1918 flu pandemic have had such a wide range of effects over such a brief period of time, including fatalities. Unfortunately, we should brace ourselves for more significant disruptions in the future. The Corona virus has a serious impact on the construction sector, which is the second-most significant sector among all sectors contributing to India's GDP. This paper focuses on the impact of this global epidemic on the world and Indian constructing industries. It also emphasizes the significance of civil engineering & town planning in reducing the pandemic's impact on the construction industry and resuming normal operations with appropriate remedies and mitigation strategies for all sectors that depend on the building industry. After the Corona virus, the future of the building industry is also briefly considered. The moment has come for us to pull up our socks and start searching for more effective planning for the future, not just for urban regions but also for slums, if we want to salvage the future after lockdown. Everyone has a lot to learn from the pandemic. Construction firms should work to make their business models more resilient as they design their recovery roadmaps, and they may concentrate more on plug-and-play solutions such prefabricated ducts & utilities, etc., to enhance the quality and efficiency of project execution. Early in 2020, the COVID-19 pandemic broke out, posing significant problems for the world economy and having an impact on many different sectors. Even the resilient building and engineering industry was susceptible to the pandemic's devastating effects. The multiple effects of COVID-19 upon the construction as well as engineering industries are thoroughly examined in this paper, encompassing disruptions to supply chains, shortages of workers, project delays, financial limitations, and the adoption of creative mitigation techniques. Paper also focuses on the adapting actions made by industry players and offers insights into probable long-term changes and future prospects for the building and engineering industry